Respuesta :

Given:

There are given the expression:

[tex](3w+5)(-2w-7)[/tex]

Explanation:

According to the question:

We need to find the value of multiplication by using the distributive property:

So,

From the property of distributive low:

[tex]a(b+c)=ab+ac[/tex]

Then,

From the expression:

[tex](3w+5)(-2w-7)=(3w+5)(-2w)+(-7)(3w+5)[/tex]

Then,

[tex]\begin{gathered} (3w+5)(-2w-7)=(3w+5)(-2w)+(-7)(3w+5) \\ =-6w^2-10w+(-21w)-35 \\ =-6w^2-10w-21w-35 \\ =-6w^2-31w-35 \end{gathered}[/tex]

RELAXING NOICE
Relax